2020
DOI: 10.3201/eid2610.201800
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Sensitive, Full-Genome Sequencing of Severe Acute Respiratory Syndrome Coronavirus 2

Abstract: We describe validated protocols for generating high-quality, full-length severe acute respiratory syndrome coronavirus 2 genomes from primary samples. One protocol uses multiplex reverse transcription PCR, followed by MinION or MiSeq sequencing; the other uses singleplex, nested reverse transcription PCR and Sanger sequencing. These protocols enable sensitive virus sequencing in different laboratory environments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(123 citation statements)
references
References 10 publications
3
120
0
Order By: Relevance
“…We observed that the RT-LAMP assay was less sensitive and informative than multiplex PCR-based NGS in our study and other literature (20)(21)(22)(23)(24). NGS is a robust tool for obtaining extensive genetic information, allowing LOD values as low as 10 copies/ml for SARS-CoV-2 and serving as a reference test for COVID-19, especially for those challenging samples with a low viral content (2,(22)(23)(24). However, several experimental issues, such as erroneous barcode sequencing, the production of primer dimers, and potential cross-contamination between runs, may complicate sequence-based analyses and impact the validity of NGS results (25,26).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We observed that the RT-LAMP assay was less sensitive and informative than multiplex PCR-based NGS in our study and other literature (20)(21)(22)(23)(24). NGS is a robust tool for obtaining extensive genetic information, allowing LOD values as low as 10 copies/ml for SARS-CoV-2 and serving as a reference test for COVID-19, especially for those challenging samples with a low viral content (2,(22)(23)(24). However, several experimental issues, such as erroneous barcode sequencing, the production of primer dimers, and potential cross-contamination between runs, may complicate sequence-based analyses and impact the validity of NGS results (25,26).…”
Section: Discussionsupporting
confidence: 55%
“…We observed that the RT-LAMP assay was less sensitive and informative than multiplex PCR-based NGS in our study and other literature (20)(21)(22)(23)(24). NGS is a robust tool for obtaining extensive genetic information, allowing LOD values as low as 10 copies/ml for SARS-CoV-2 and serving as a reference test for COVID-19, especially for those challenging samples with a low viral content (2,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 48%
“…The present study does have several limitations. First, the 4 methods were tested on a limited number of European samples, all affiliated to the lineage B1, according to the Pangolin classification (23); the present evaluation should be confirmed in larger studies including other lineages in order to be more representative of the global ecology of this emerging virus.As SARS-CoV-2 sequencing is an expanding market and other methods has been published(24)(25)(26) or are probably under development, the present study is not exhaustive. However, the approaches selected herein are representative of the methods mostly used during pandemics and are easy to implement in a diagnostic laboratory.…”
mentioning
confidence: 99%
“…To conserve resources, pools with up to five specimens were tested together, and individual specimens within positive or inconclusive pools were retested. Nucleic acid from RT‐PCR–positive specimens was then extracted and subjected to Oxford Nanopore MinION sequencing, and full genome sequences were generated using methods described previously 3 . Phylogenetic relations were inferred using the Nextstrain pipeline, 4 including the 36 positive SARS‐CoV‐2 sentinel specimens and selected full genome sequences available as of April 1, 2020, from the Global Initiative on Sharing All Influenza Data (GISAID) 5 .…”
Section: Characteristic Age Group All Ages <18 Years Wk Beginning Marmentioning
confidence: 99%